2019
DOI: 10.1155/2019/5047463
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Reversible Effects on Altered Default Mode Network of Chronic Migraine Accompanied with Clinical Symptom Relief

Abstract: Objective. To determine whether and how longitudinal acupuncture modulates the impaired default mode network (DMN) in chronic migraine (CM) patients without aura. Methods. Resting-state functional magnetic resonance imaging (fMRI) data from 14 CM patients treated with longitudinal pre- and postacupuncture treatment (PPAT) and data of 18 age- and gender-matched healthy controls (HCs) were analyzed using independent component analysis (ICA) and seed-based correlation analysis (SCA) to investigate connectivity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 29 publications
2
54
1
Order By: Relevance
“…More and more studies confirmed that abnormal FC between the limbic system and DMN was related to pain, so regulating their FC could alleviate pain, which is supported by the results of analgesic treatment research. Zou [ 53 ] suggested acupuncture could reduce the FC within DMN to a healthy control level in chronic migraine patients, and the FC between DMN and limbic system also decreased in chronic pain patients after cognitive behavioral therapy [ 54 ]. Furthermore, Fang [ 55 ] found that compared with staVNS, the FC decreased between the DMN and limbic system after one-month taVNS, suggesting that taVNS can regulate the FC between the limbic system and DMN.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies confirmed that abnormal FC between the limbic system and DMN was related to pain, so regulating their FC could alleviate pain, which is supported by the results of analgesic treatment research. Zou [ 53 ] suggested acupuncture could reduce the FC within DMN to a healthy control level in chronic migraine patients, and the FC between DMN and limbic system also decreased in chronic pain patients after cognitive behavioral therapy [ 54 ]. Furthermore, Fang [ 55 ] found that compared with staVNS, the FC decreased between the DMN and limbic system after one-month taVNS, suggesting that taVNS can regulate the FC between the limbic system and DMN.…”
Section: Discussionmentioning
confidence: 99%
“…Main findings AD [38] Cognition regions AD [39] Hippocampal Depression [40] Limbic system, amygdala, and the ACC CM [41] DMN Stroke [42] Bilateral motor cortex Stroke [43] Motor-related network MCI [44] Cognition regions Ischemic stroke [45] Sensorimotor network Depression [40] Limbic system, amygdala, and ACC Stroke [46] PM/SMA and SMG RFPN Migraine [47] ACC and PCC Stroke [48] chronic pain [49][50][51] Networks: DMN, salience, central executive, and sensorimotor ALBP [52] Limbic, pain, attentional and somatosensory system, and DMN CD [53] Afferent processing network and DMN Smoking craving [54] SN Hypertension [55] Frontal lobe, cerebellum, and insula PMS [56] Aberrant neural activity Cardiovascular [57] Cortical, hypothalamus and brainstem stimulation; and specific visualization of acupoints. Specifically, the following conclusions can be drawn from the physiological mechanism of acupuncture at acupoints and its specificity research: there are differences in the brain connectivity and local activities between single and different acupoints, and combination points have more wide activate areas than single point; the regulate areas are mostly related to the emotional, cognitive, and painful functions; limbic system and subcortical areas are found to be hubs after acupuncture; verum acupuncture may increase DMN, PAG, PCC, and pain matrix connectivity compared with sham acupuncture, and sham acupuncture influenced less functional areas than true acupuncture; the local brain functional activities of ipsilateral acupuncture are different from those of contralateral acupuncture; the effect of acupuncture has an obvious individual difference; and there are different degrees of changes in brain functional connectivity among different acupunctures, intensities, methods, and different subjects, and an adjusting acupuncture approach can be used as a means of regulating brain activity.…”
Section: Dominant Diseasesmentioning
confidence: 99%
“…Due to the particularity of acupuncture treatment, this study adopted a randomized, single-blind study. According to the previous study [15,19], the estimated sample size was 30. The randomized digital table method combined with the random number remainder grouping method was used to randomly group the patients by a specialized statistical expert.…”
Section: Mri Data Preprocessing and Functional Connectivitymentioning
confidence: 99%